2022
DOI: 10.3390/su142416671
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood Capital, Ecological Cognition, and Farmers’ Green Production Behavior

Abstract: Green development of agriculture is inevitable to meet the objective demand of rural ecological environment protection and high-quality agricultural development. Livelihood capital is the basic condition for farmers to carry out the activities of production and management, while ecological cognition is the direct motivation for their behaviors. Based on field research data from 436 farm households in 4 counties of Langao, Fuping, Mian, and Yaozhou in Shaanxi Province, China, the study conducted the double-hurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Unlike them, we found that cotton farmers' intrinsic perceptions of green production and external regulations are mediating variables that affect their adoption of AGPTs. O'Connor and Assakerd et al empirically verified the mechanisms through which farmers' green perceptions influence their adoption of AGPTs [83][84][85]. Similarly, this paper confirms the effect of green perceptions on green production technology adoption behavior and its internal mechanisms.…”
Section: Similarities and Differences With Existing Studiessupporting
confidence: 74%
“…Unlike them, we found that cotton farmers' intrinsic perceptions of green production and external regulations are mediating variables that affect their adoption of AGPTs. O'Connor and Assakerd et al empirically verified the mechanisms through which farmers' green perceptions influence their adoption of AGPTs [83][84][85]. Similarly, this paper confirms the effect of green perceptions on green production technology adoption behavior and its internal mechanisms.…”
Section: Similarities and Differences With Existing Studiessupporting
confidence: 74%
“…However, factors such as the age of respondents, family farmland area, health status, and the proportion of family labor did not have a significant impact on farmers' enthusiasm for adopting digital agricultural extension services, possibly because they are not decisive factors in farmers' actual production processes [49]. For example, while older farmers may traditionally have a lower acceptance of new technologies, the high level of information technology and popularization in modern society has enabled farmers of all ages to access digital agricultural extension services [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still limited empirical evidence on the impact of farmers' cognition on the adoption of digital agricultural extension services. Most studies on farmers' cognition focus on the effect of single-dimensional cognition, such as risk perception, income perception, ecological perception, and technology perception, on agricultural technology adoption [11][12][13][14][15][16][17][18]. For digital agricultural extension services, most studies focus on qualitative research on the current status, problems, and advantages [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, livelihood capital is the central aspect of the sustainability analysis framework and includes the following five components: natural capital, physical capital, financial capital, human capital, and social capital, which influence the formation of livelihood strategies to different degrees. The research conducted by applying the sustainability analysis framework has extensively covered many cross-cutting disciplines such as tourism industry, macroeconomic analysis, social infrastructure, and migration issues [59][60][61][62].…”
Section: Data Sourcementioning
confidence: 99%